Association between HbA1c and Non-HDL-Cholesterol in Type 2 Diabetes Mellitus at a Tertiary Hospital in Indonesia - Putri, Karina Widya; Soelistijo, Soebagijo Adi; Prabowo, Gwenny Ichsan (Cardiovascular and Cardiometabolic Journal (CCJ), 2025)
Abstract: Diabetic dyslipidaemia is considered a modifiable risk factor for cardiovascular disease (CVDs). Non-high-density lipoprotein-cholesterol (non-HDL-C) is a better predictive measure of CVD compared to glycosylated haemoglobin (HbA1c) in type 2 diabetic. This study aims to explore the intricate link between these variables, which contribute significantly to the health risks of T2DM, particularly in a clinical environment like Dr. Soetomo's Endocrinology Polyclinic. Material and Methods: This study used a cross-sectional method with observational analytics design to determine the correlation between HbA1c and non-HDL cholesterol in Type 2 Diabetes Mellitus. Data was collected at Dr. Soetomo Surabaya's Endocrinology Polyclinic from April 2022 to May 2023, focusing on medical records of Type 2 Diabetes Mellitus (T2DM) patients with dyslipidaemia. The study involved T2DM outpatients meeting specific criteria and excluded those with incomplete records or stage 5 Chronic Kidney Disease (CKD) diagnosis at the clinic. The data processing utilized the SPSS statistical program to examine the correlation between independent and dependent variables, employing Pearson or Spearman Correlation based on the data's distribution. Results: The study included mostly women (66.67%) averaging 52.11 years old (SD 4.61). Simvastatin was the most prescribed statin (60.92%). Mean values for HbA1c, total cholesterol, HDL, LDL, and non-HDL cholesterol were 8.155%, 217.29 mg/dL, 46.61 mg/dL, 141.37 mg/dL, and 170.68 mg/dL. Most had poor glycemic control and cholesterol ≥ 130 mg/dL. The Spearman test showed a strong positive correlation between HbA1c and non-HDL cholesterol (r=0.534; p<0.001) and a moderate positive correlation with LDL cholesterol (r=0.473; p<0.001). Conclusion: There is a strong correlation between HbA1c and non-HDL cholesterol in Type 2 Diabetes Mellitus. -- Highlights: 1. A significant positive correlation was observed between HbA1c and non-HDL cholesterol levels in patients with Type 2 Diabetes Mellitus, indicating a linked progression of glycemic and atherogenic profiles. 2. The findings support non-HDL cholesterol as a reliable and cost-efficient parameter for assessing cardiovascular risk, complementing or surpassing LDL cholesterol in clinical evaluation.